The effect of opium addiction on serum adiponectin and leptin levels in male subjects - Shahouzehi, Beydolah; Shokoohi, Mostafa; Najafipour, Hamid (Technische Universität Dortmund, 2013)
Serum adiponectin and leptin levels have been shown to be related to obesity, insulin resistance and cardiovascular diseases (CVD). Opium addiction has a positive association with endocrine system disorders. The relationship between adipokines and opium addiction is unclear. In the present study, we aimed to determine serum adiponectin and leptin levels in opium addicted subjects. Methods: 176 men, 88 opium addicts and 88 non-addicts were randomly selected from subjects who participated in Kerman Coronary Artery Disease Risk factors Study (KERCADRS); a population-based study. Serum adiponectin and leptin levels were measured using ELISA and compared between two groups. We adjusted the effect of some confounding factors such as the patients’ demographic, clinical and medical history in multivariate analysis model. Results: The serum level of adiponectin in opium addicts was significantly lower than control group (6.5±3.6 vs. 9.8±8.1 μg/ml, P<0.001). There was no significant difference in serum leptin level between two groups (11.8±10.3 ng/ml in control group vs. 11.5±10.8 ng/ml in opium addicts, p = 0.80). In the multivariate analysis, after adjusting for age, cigarette smoking, body mass index, type 2 diabetes, hypertension, cholesterol, triglyceride and high and low density lipoproteins, the negative association between opium addiction and decreased adiponectin level was still present (β = -0.144, P value = 0.005). Conclusions: The results showed that opium addiction reduces serum adiponectin level. Since adiponectin has been shown to have anti-diabetic and anti-atherogenic effects, its reduction may account for increase in the risk of metabolic disorders such as insulin resistance and CVD amongst opium addicted patients.
a case control study from Kerman Coronary Artery Disease Risk factors Study (KERCADRS)
EXCLI Journal ; Vol. 12, 2013
Keywords: Opium addiction; leptin; adiponectin; cardiovascular diseases; 610